Hybrid Grid Partitioning and Fuzzy Goal Programming Model To Production Planning Problems Approach - Poongothai Scott Özcan; Kouvelis Hocine Garetti (International Journal of Enterprise Modelling, 2021)
The Hybrid Grid Partitioning and Fuzzy Goal Programming model is a novel method for solving production planning issues that is presented in this study. The model combines the spatial characteristics-capturing Grid Partitioning approach with the handling fuzzy goals and constraints-handling Fuzzy Goal Programming. The study offers a mathematical formulation and a numerical example to show how well the model performs in terms of capacity considerations, optimizing resource allocation, and incorporating subjective preferences using fuzzy membership functions. The results emphasize the model's potential benefits for optimizing resource utilization, handling uncertainties, and production planning decision-making. However, there are certain drawbacks, including oversimplified assumptions, scalability issues, and insufficient validation. Future studies should look at these issues and determine whether the model can be used in actual production settings. Overall, the Hybrid Grid Partitioning and Fuzzy Goal Programming model provides a thorough framework for production planning that incorporates geographic factors and fuzziness in the optimization process.